MORE EFFECTIVE SCREENING FOR EPIRETINAL MEMBRANES WITH MULTICOLOR SCANNING LASER OPHTHALMOSCOPE THAN WITH COLOR FUNDUS PHOTOGRAPHS. Issue 7 (July 2020) - Terasaki, Hiroto; Sonoda, Shozo; Shiihara, Hideki; Kakiuchi, Naoko; Funatsu, Ryoh; Shirasawa, Makoto; Sakamoto, Taiji
Abstract : Purpose: To assess the ability of the multicolor scanning laser ophthalmoscope (MC-SLO) to screen for epiretinal membranes (ERMs). Methods: A retrospective cross-sectional study of 35 eyes of 32 patients with an ERM detected by optical coherence tomography and 46 eyes of 23 healthy volunteers. The detection of the ERM was graded into three visibility scores—1, not visible, 2, barely visible, and 3, clearly visible—by retina specialists or by ophthalmology residents. The sensitivity and specificity of the detection with the merged image of the MC-SLO or color fundus photographs (CFPs) were calculated. Results: The sensitivity for ERM detection in the MC-SLO and CFP were 91.4% and 65.7% by specialists and 97.1% and 60.0% by residents. The specificity for both devices was 100% by specialists and residents. The visibility score for the MC-SLO images were significantly higher than that for the CFP by both specialists and residents. In addition, the visibility score for the MC-SLO determined by residents was significantly higher than that for the CFP by specialists. Conclusion: The detection of an ERM is better with the MC-SLO images than with CFP. Furthermore, the ERM detection in the MC-SLO images by residents was comparable to that by specialists. Abstract : The ability of the multicolor scanning laser ophthalmoscope to screen for epiretinal membranes was studied. The detection of an epiretinal membrane in the multicolor scanning laser ophthalmoscope images by ophthalmology residents has good sensitivity/specificity and was comparable to that by the retina specialists.